2002
DOI: 10.1063/1.1436468
|View full text |Cite
|
Sign up to set email alerts
|

Magnitude and orientation dependence of intermolecular interaction between perfluoroalkanes: High level ab initio calculations of CF4 and C2F6 dimers

Abstract: Intermolecular interaction energies of eight orientation CF4 dimers and seven orientation C2F6 dimers were calculated with electron correlation correction by the second-order Møller–Plesset perturbation (MP2) method. The D3d CF4 dimer and C2h C2F6 dimer have the largest binding energies. Electron correlation correction increases the attraction considerably, while the effects of electron correlation beyond MP2 are small. Electrostatic and induction energies are not large in all cases. This indicates that disper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
64
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(70 citation statements)
references
References 28 publications
5
64
1
Order By: Relevance
“…These models also give good overall agreement with the quantum chemistry results 11,12 for dimer energies, as shown in Table 5. The F3 case was already discussed by Tsuzuki et al 12 who concluded that this AA model was a definite improvement on the UA models.…”
Section: Discussionsupporting
confidence: 73%
“…These models also give good overall agreement with the quantum chemistry results 11,12 for dimer energies, as shown in Table 5. The F3 case was already discussed by Tsuzuki et al 12 who concluded that this AA model was a definite improvement on the UA models.…”
Section: Discussionsupporting
confidence: 73%
“…[52][53][54][55][56][57] In this work, we update the reference data for this last set of 17 complexes, to ensure that the full KB49 set of reference data will be of consistently high quality. The updated BEs are collected in Table I, grouped by the dominant interaction type.…”
Section: B Ab Initio Reference Datamentioning
confidence: 99%
“…[3] CF 3 -groupsa ppear not to repel other negatively polarized groups as strongly as expected and even to enter into "negative-negative" close contacts,m any between CF 3 -groups( self-dimerization). [5] The strongestF ···F interaction reported for the CF 4 dimer is À0.7 kcal mol À1 , [6][7][8] and the energy of as ingle F···F interaction between CF 4 molecules has been estimated to be À0.2 kcal mol À1 . [5] The strongestF ···F interaction reported for the CF 4 dimer is À0.7 kcal mol À1 , [6][7][8] and the energy of as ingle F···F interaction between CF 4 molecules has been estimated to be À0.2 kcal mol À1 .…”
Section: Introductionmentioning
confidence: 99%
“…[4] NMRr esultss uggest these interactions are strong enough to hinder rotationo ft he CF 3 groups in solution. [8] Since CF 4 does not have ap ermanentd ipole,t he F···F interactions have been suggested to result primarily from dispersion, althoughe lectrostatic interactions may [8] or may not [6] also play as ignificant role. [8] Since CF 4 does not have ap ermanentd ipole,t he F···F interactions have been suggested to result primarily from dispersion, althoughe lectrostatic interactions may [8] or may not [6] also play as ignificant role.…”
Section: Introductionmentioning
confidence: 99%